A participação das transferências intergovernamentais no crescimento econômico dos municípios: um estudo no estado de Santa Catarina - Moratta, Nelson Granados (2015)
The present study primarily aims at identifying budget (in) dependence concerning inter- governmental transfers and their effect on the economic growth of municipalities having up to 10,000 inhabitants in the State of Santa Catarina, Brazil. As secondary objectives, it aims at: studying the Brazilian State operational method from its fiscal federalism point of view through measuring the relationship between inter-governmental transfers and municipality total tax collection: and, analyzing inter-governmental transfer participations in the municipality tax collection, also considering their respective Gross Domestic Product (GDP) variations. To help understanding the subject at issue, we provide explanations of the State and Public Administration performances, Public Finances, Public Budget, economic growth and development. The study relevance lies in the fact that small municipalities have tax collection problems and inter-governmental transfers are vital for their survival. The total amount deriving from both resources greatly affects economic growth, thus we intend to show that inter-governmental transfers are essential to small municipalities. The research methodology is descriptive, bibliographic and documental focusing on the theoretical referential landmark. According to the research sample average, results show that municipalities depend on transfers, mainly from the Federal Government, that represented over 89% between 2008 and 2012, except for 2010 when they were equivalent to 76.38%. GDP during our research period was -11% showing that dependence on inter-governmental transfers does not affect the municipality economic growth.